Raising pragmatic awareness: A think-aloud study. (June 2021) - Timpe-Laughlin, Veronika; Green, Ashley; Oh, Saerhim
Abstract: This paper reports findings from a think-aloud study that explored the effectiveness of Words at Work, a learning platform intended to aid adult English-language learners in becoming (more) aware of pragmatics in the context of the U.S. workplace. Twenty participants engaged with Words at Work in a computer laboratory. They were asked to (a) think aloud while solving pragmatics tasks (pretest), (b) engage with a Words at Work unit, and (c) complete a parallel form of the pretest pragmatics task, again thinking aloud while solving the tasks (posttest). The audio-recorded verbal reports were transcribed and coded inductively for pragmatic-related episodes (PREs), instances where participants mentioned relevant pragmalinguistic or sociopragmatic aspects. Frequency counts were tabulated for all PREs, and paired-sample t -tests were conducted to investigate differences between pre- and posttest results. Findings revealed statistically significant increases in PREs in the post-think-alouds. In addition to highlighting a change in cognitive state, we observed a key aspect of raising L2 learners' pragmatic awareness: the need to provide learners with the vocabulary to talk about how they use language. Findings are discussed in terms of their implications for the construct of metapragmatic awareness and effectively designing environments to promote pragmatic awareness.